FİBROMYALJİDE NETRİN 1 VE RESEPTÖRLERİNİN AKTİVİTELERİNİN DEĞERLENDİRİLMESİ - KÖHLE, ALPARSLAN (Fırat Üniveristesi, 2017)
Bu çalışmada fibromyalji (FM) ve osteoartrit gibi non-inflamatuar romatizmal hastalıklarda serum Netrin 1 düzeyi ve netrin reseptörlerinin düzeylerinin belirlenmesi amaçlandı. 1990 ACR tanı kriterlerine göre tanı almış 50 FM'li kadın hasta ve 50 osteoartrit tanılı hasta alındı. İlaveten, 50 sağlıklı gönüllü ile kontrol grubu oluşturuldu. Katılımcıların serum örneklerinden; Netrin 1, netrin reseptörleri (DCC, UNC5B ve UNC5D), IL (interlökin)-6, IL-10 ve IL-17'nin düzeyleri ELISA yöntemiyle analiz edildi. Serum Netrin 1 düzeyi FM grubunda hem kontrol hem de osteoartrit grubundan anlamlı düşüktü (sırasıyla; p<0.01 ve p<0.001). Ancak, osteoartritli hastalar ile sağlıklı bireyler arasında istatistiksel olarak anlamlı bir fark yoktu (p>0.05). Diğer taraftan, FM grubunda, netrin reseptörlerinin ve sitokinlerin serum düzeyleri artmamıştı (p>0.05). Ancak, serum DCC ve UNC5D düzeyleri ile IL-6 ve IL10 düzeyleri osteoartrit grubunda yüksekti (sırasıyla; p<0.001, p<0.05, p<0.01 ve p<0.001). Sonuç olarak, FM'de serum Netrin 1 düzeyi baskılanmaktadır. Bu bulgu, Netrin 1'in hastalık patogenezinde etkin olduğunu düşündürmektedir.

The aim of this study was to determine the serum levels of Netrin 1 and its receptors in patients with non-inflammatory diseases those are fibromyalgia (FM) and osteoarthritis. The study included 50 female patients with FM fullfilling the 1990 ACR diagnostic criteria, and 50 patients with osteoarthritis. Moreover, control group consisted of 50 healthy female volunteers. In sera harvested from the participants, Netrin 1, netrin receptors (DCC, UNC5B and UNC5D), IL (interluekin)-6, IL-10 and IL-17 levels were analysed by ELISA method. In the FM group, serum Netrin 1 level was decreased compared to the both control and osteoarthritis groups (p<0.01 and p<0.001 respectively). However, there was no significant difference between the control and osteoarthritis groups in terms of serum Netrin 1 level (p>0.05). On the other hand, serum netrin receptors levels and cytokines levels were similar in the FM and control groups (p>0.05). However, in the osteoarthritis group, serum DCC and UNC5D levels; moreover, serum IL-6 and IL10 levels were higher compared to the control group (p<0.001, p<0.05, p<0.01 and p<0.001, respectively). In conclusin, serum Netrin 1 level is decreased in FM. This finding suggests that Netrin 1 may have prominet role in the disease pathogenesis
Evaluations of netrin 1 and receptor activity in fibromyalgia
Keywords: Romatoloji